Pengaruh Nilai Laba Dan Nilai Buku Terhadap Relevansi Nilai Dengan Pengungkapan Corporate Social Responsibility Sebagai Variabel Moderating (Studi Pada Perusahaan Manufaktur di Bursa Efek Indonesia Periode Tahun 2010-2014) - Permatasari, Wulan Indah, Dra. Rina Trisnawati, Ak, M.Si, Ph.D (2016)
This study aims to determine the disclosure of Corporate Social Responsibility (CSR) as moderating variable on the value relevance of earnings and book value. Earnings is measured by earnings per share (EPS) and book value is measured by the net asset value per share. The regression model used was Ohlson Earnings Model. While the value relevance proxied by stock prices. Measurement of corporate social responsibility based on the Global Reporting Intiatives disclosure index (GRI) 2013 as seen from the company's annual report. The population of this research is all manufacturing companies listed in Indonesia Stock Exchange (BEI) 2010-2014. Sample used purposive sampling technique by 13 companies during 5 years of observation. So the total sample was 65. The data analysis used classical assumption testing multiple linear regression method. The results showed that the value of earnings and book value has value relevance. CSR disclosure moderating value relevance of book value but does not moderating the value relevance of earnings.